Science and innovation with stratospheric balloons: the Olimpo & Lspe/swipe projects - Volpe, A.; Albano, M.; Ade, Peter; Baldini, A. M.; Baù, A.; Battistelli, E.; de Bernardis, P.; Biasotti, M.; Boscaleri, A.; Cei, F.; Colantoni, I.; Columbro, F.; et al. (Aerotecnica Missili & Spazio, 2023)
The measurement of the Cosmic Microwave Background (CMB) polarization and the spectral distortions produced on this radiation field by clusters of galaxies (Sunyaev-Zeldovich Effect, SZE) are the current frontiers in cosmology. In this paper, we report on two stratospheric balloon experiments aimed to study the research fields mentioned above. OLIMPO is a mm/submm waves telescope, with 2.6 m primary mirror coupled to four arrays of Kinetic Inductance Detectors (KID), centered at 150, 250, 350, and 460 GHz, to match the SZ spectrum, and operating at 0.3 K. The payload, flown in 2018 producing a very successful technology demonstration, includes a plug-in Differential Fourier-Transform Spectrometer. LSPE (Large Scale Polarization Explorer) is a combined balloon-borne and ground-based program dedicated to the measurement of the CMB polarization at large angular scales. LSPE/SWIPE (Short Wavelength Instrument for the Polarization Explorer), the balloon-borne instrument, includes a refractive telescope with a 50 cm optical aperture feeding three arrays of 330 multi-mode TES bolometers at 145, 210, e 240 GHz. The polarization of the incoming radiation will be modulated by a rotating Half Wave Plate (HWP), that is maintained levitating by an innovative magnetic suspension system. The detectors and the optical elements are cooled at cryogenic temperatures. The cryogenic system is designed to have a duration of 14 days with a flight performed during the polar night, to allow a coverage of a large fraction of the sky. In the paper, we describe the configuration of the two instruments, the modifications to be implemented on OLIMPO for a second scientific flight and the status of the different sub-system for LSPE/SWIPE.